Aprovechamiento de residuos generados del procesamiento de trucha arcoíris (Oncorhynchus mykiis) y tilapia gris (Oreochromis niloticus) para la elaboración de balanceado para pollos en etapa de crecimiento - Manobanda Quicaliquin, Roxana Vanesa (2024)
The objective of the research was to take advantage of the waste generated from the processing of rainbow trout (Oncorhynchus mykiis) and gray tilapia (Oreochromis niloticus) for the production of feed for chickens in the growing stage. The research was carried out in the Research and Linkage laboratories, Agroindustrial Complex of the State University of Bolívar. The waste from rainbow trout and gray tilapia were subjected to a physical analysis with the following results: the waste from rainbow trout has a humidity of 71.06% and ash 6.21%, the waste from gray tilapia has a moisture content 68.23% and 9.29% ash. These residues were evaluated through a complete randomized experimental design in AxBxC factorial arrangement (2x2x2) with 8 treatments and two replicates, where factor A has levels a1 rainbow trout residues, a2 gray tilapia residues, factor B has levels b1 50 °C, b2 60 °C and the factor C has the levels c1 tray drying, c2 circular drying. The treatments were evaluated with the variable response of % protein in the flour obtained, with the best treatment being T4 subjected to 60 °C in the circular rainbow trout waste dryer, which contains 72.75% protein. In the bromatological analysis, the flour showed a moisture content of 5.50%, ash 11.27%, fat 17.16%, fiber 6.22% and protein content 72.75%, within the microbiological analysis it was observed the absence of mold and yeast microorganisms, salmonella and coliform count. For the formulation of the balance, corn flour, soy flour, rice dust, wheat bran, trout flour (T4), palm oil and mineral salt were used. The microbiological analysis of the prepared feed showed an absence of microorganisms, showing that it complies with the INEN 1829 regulations for zootechnical foods. The bromatological analysis of the balance showed 10.12% moisture, 9.19% ash, 9.23% fat, 9.31% fiber and 16.22% protein. The balance was tested on broiler chickens to determine its effectiveness, obtaining an average weight gain of 34.74 g to 42 g in their growth stage.